Promoting agriculture amongst the black youth of South Africa : the role the sector has to play in creating employment, alleviating poverty, and achieving equitable economic growth - Mama, Mlungisi Lungile (Stellenbosch : Stellenbosch University, 2020)
Thesis (MCom)--Stellenbosch University, 2020.